Pemanfaatan media pembelajaran Phet simulation dalam eksperimen fisika - Dasmo Dasmo; Yoga Budi Bhakti; Napis Napis (Navigation Physics : Journal of Physics Education, 2019)
The experiment of determining the value of the Planck constant using Simulation Based Laboratory is done in order to compare the value of the Planck constant in theory to the value of the Planck constant through experimentation. This experiment wpas done using PhET simulations. Photoelectric effect is an event where when a beam or photon is worn on a substance, it will release the electron and the electric current. In the equation of photoelectric effect, the most important is a constant, the Planck constant. The result of the experiment obtained the Planck constant value is J. s with a relative error of 0.15%, while based on the theory of the value of the constant Planckis J. S can be concluded that the results of the experiment carried out close to the theory.